Fiancées and widows: women’s encounters with death in the silent films of Fritz Lang - Kłys, Tomasz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Kłys Tomasz, Fiancées and widows: women’s encounters with death in the silent films of Fritz Lang. “Images” vol. XXV, no. 34. Poznań 2019. Adam Mickiewicz University Press. Pp. 155–162. ISSN 1731-450X. DOI 10.14746/i.2019.34.10. In the silent Weimar films of Fritz Lang, the heroines have sudden encounters with Death, conceived both as an allegorical figure and as an unexpected violent end of the life of their fiancé, husband or loved one. The nameless Maiden, the main heroine of Der müde Tod (The Weary Death, known in English-language countries as Destiny, 1921), while looking for her fiancé, who was kidnapped by Death, tries three times to regain his life and finally, overcome by Death, commits suicide. Two queens of Burgundy in Die Nibelungen (The Nibelungs, 1924), Kriemhild and Brunhild, motivated by resentment and vengeance, as well as by unfulfilled love, finally appear to be zombie-like self-destructive monsters, destroying the social and political order, and the lives of many human beings. The paper, with the use of the psychoanalytic concepts of melancholy and the mourning “not-worked-out” by the persons who have lost their loved ones, analyses the ambiguous attitudes and self-destructive acts of these “women in black”..